DETERMINACIÓN SEROLÓGICA DE LA INFECCIÓN CON Mycoplasma hyopneumoniae EN UNA GRANJA PORCINA DE LIMA - Calle E., Sonia (2006)
A serological study was conducted to identify the age of highest infection with Mycoplasma hyopneumoniae in pigs under an intensive rearing system in the Lima province, during the period April – August, 2002. Blood samples were collected fortnightly from birth till 16 months of age in 30 piglets. The commercial test ELISA Chekit®-Hyoptest- II was used for the detection of antibodies. The 66.3% (20/30) of the animals showed antibodies against M. hyopneumoniae. The critical period for starting the infection occurred at 9-10 weeks of age. Sex and number of parturition did not affect the time of initial infection.